Spontaneous Regression of a Symptomatic Cyst of the Cavum Septi Pellucidi and Vergae - Krejčí, Tomáš; Krejčí, Ondřej; Lipina, Radim (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Spontaneous regression of cysts of the cavum septi pellucidi (CSP) and cavum vergae (CV) is rare and little discussed. The authors present their case report of this phenomenon following a severe headache in a 23-year-old woman, in whom magnetic resonance imaging (MRI) had previously confirmed significant thinning of the left lateral cyst wall. We consider this finding to be a possible predisposing factor to rupture and the spontaneous regression of such cysts. In addition to the mechanism of cyst regression, the interrelated causes of their expansion and formation will be discussed.
Keywords: cavum septum pellucidum; cavum vergae; cyst; endoscopic fenestration; spontaneous regression